2020
DOI: 10.3390/app10134456
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Biomedical Imaging of Periiliac Adipose Tissue Identifies Perivascular Fat as a Marker of Disease Complexity in Patients with Lower Limb Ischemia

Abstract: The aim of the study was to develop a semi-automated, computer-aided imaging technique to quantify the amount and distribution of perivascular fat at the level of the iliac arteries (periiliac adipose tissue—PIAT), and to investigate the association of this new computer-aided imaging biomarker with other biomedical imaging biomarkers, which characterize the pelvic adipose tissue (SAT—subcutaneous adipose tissue; VAT—visceral adipose tissue). We included 34 patients with peripheral arterial disease, in whom the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Patients with DM had more but less dense peri-aortic adipose tissue, suggesting the presence of larger hypertrophic adipocytes. As far as we know, no study has reported that patients with DM have a higher quantity of peri-aortic adipose tissue around the abdominal aorta, but it has been described that diabetic subjects have more peri-aortic adipose tissue around the thoracic aorta [47]. Ömer et al concluded that the quantity of adipose tissue that surrounds the thoracic aorta was positively correlated with HbA1c [48].…”
Section: Characteristics Of Adipose Tissue Depot and Cardiovascular R...mentioning
confidence: 99%
“…Patients with DM had more but less dense peri-aortic adipose tissue, suggesting the presence of larger hypertrophic adipocytes. As far as we know, no study has reported that patients with DM have a higher quantity of peri-aortic adipose tissue around the abdominal aorta, but it has been described that diabetic subjects have more peri-aortic adipose tissue around the thoracic aorta [47]. Ömer et al concluded that the quantity of adipose tissue that surrounds the thoracic aorta was positively correlated with HbA1c [48].…”
Section: Characteristics Of Adipose Tissue Depot and Cardiovascular R...mentioning
confidence: 99%